Hybrid Versus Conventional Treatment of Acute Type A Aortic Dissection. Issue 9 (22nd July 2015) - Settepani, Fabrizio; Cappai, Antioco; Basciu, Alessio; Barbone, Alessandro; Citterio, Enrico; Ornaghi, Diego; Tarelli, Giuseppe
Abstract Background To determine whether the hybrid approach to acute type A aortic dissection results in improved outcomes in terms of mortality, neurologic complications, need for distal aortic reintervention, and false lumen thrombosis compared with the conventional approach. Methods Data from comparative studies of hybrid versus conventional treatment of acute type A aortic dissection were combined through meta‐analysis. Pooled odd ratios were calculated using random effects models. Results Seven comparative studies including 967 patients were identified; of these, 503 underwent conventional proximal aortic repair and 429 extensive distal aortic repair including a stented elephant trunk technique. Between the two groups there was no significant difference in operative mortality (p = 0.96), permanent neurologic deficit (p = 0.95), and late mortality (p = 0.59). Distal aortic repair showed a higher rate of false lumen thrombosis of the thoracic aorta (odd ratio 11.16; p < 0.001) and a reduced risk of distal reintervention (odd ratio 0.37; p = 0.01). In sub‐group analysis, frozen elephant trunk procedure showed a lower rate of distal aortic reintervention and a higher rate of false lumen thrombosis than antegrade/retrograde stent deployment techniques (p = 0.008 and <0.001, respectively). Conclusions Distal aortic repair may reduce the risk of distal reintervention and increase the rate of false lumen thrombosis without significant increase in operative mortality and permanent neurologic deficit; however, no benefit with respect to late mortality was found. The frozen elephant trunk may reduce the risk of distal aortic reintervention and may increase the false lumen thrombosis of the thoracic aorta in comparison with antegrade/retrograde stent deployment procedures. doi: 10.1111/jocs.12598 (J Card Surg 2015;30:707–713)